Representing state identity with journalistic attitudes: A corpus-assisted linguistic analysis of CGTN’s trade dispute coverage - Song, Jiannan (Círculo de Lingüística Aplicada a la Comunicación, 2024)
This research explores the relationship between journalistic attitudes and the state identity of China Global Television Network. It undertakes a corpus-assisted study of the linguistic representation of Affect, Judgment, and Appreciation in CGTN’s trade dispute coverage at two levels: (1) prosody and social actors; (2) the preference for appraisal relations. It shows that CGTN manifests its state identity in attitudinal officialization and harmonization. Highlighting collectiveness in the choice of news agendas, actors, and prosody, CGTN prioritizes the appraiser’s role of the group mind in propagating journalistic attitudes and is more inclined to draw on Judgment to stress its moral basis. A survey of the ritual of journalistic attitudes in CGTN’s trade dispute reporting makes it possible to analyze the state identity of Chinese state media.